Comparison of 2 ml (D2cc) and ICRU in image-guided brachytherapy for cervical cancer - E, Tharavichitkul; R, Jayavasti; N, Sudloy; S, Chakrabandhu; P, Klunklin; P, Onchan; B, Jia-Mahasap; P, Meuangwong; W, Nopnob; I, Chitapanarax (Biomedical Sciences and Clinical Medicine, 2020)
Objectives The use of image-guided brachytherapy (IGBT) for treatment of cervical cancer changes evaluation from point to volume with point and with volume evaluation. The purpose of IGBT is to enable a high dosage to be delivered to the tumor but to spare the surrounding tissues. This retrospective study investigated the dosages in the bladder and rectum following IGBT for cervical cancer. Methods Fourteen patients who received CT-guided brachytherapy for cervical cancer were enrolled. Whole pelvic radiotherapy (WPRT) with 45 Gy in 25 fractions plus 24-28 Gy in 4 fractions of IGBT was used. A dose of 2cc in the bladder and rectum bladder and rectum was evaluated and compared to the ICRU points in terms of EQD2. Results In the bladder, the mean dose in EQD2 of D2cc was 86.1 Gy while the mean dose to ICRU-B was 77.2 Gy. In the rectum, the mean dose in EQD2 of D2cc was 67.7 Gy while the mean dose to ICRU-R was 95 Gy. Conclusion ICRU and D2cc showed differing tendencies show different effects. In the bladder, D2cc was higher than D-ICRU but in the rectum the opposite was found.